The Influence of Leadership, Organizational Commitment on Organizational Citizenship Behavior Moderated by Job Satisfaction - Gema Bermana; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The purpose of this study was to determine the influence of leadership, organizational commitment, on Organizational Citizenship Behavior (OCB) moderated by job satisfaction  at the National Unity and Politics Agency of West Sumatra Province, Agam Regency, and West Pasaman Regency. This study used structural equations of quality with the conception of the research model path analysis which is used to analyze relationship patterns between variables with the purposed to know the direct and indirect influence of independent variables (exogenous) on the dependent variable (endogenous). The results of this study are 1) Leadership has a positive and significant influence on Organizational citizenship behavior; 2) Organizational Commitment has a positive and significant influence on Organizational citizenship behavior; 3) Job Satisfaction has a positive and significant influence on Organizational citizenship behavior; 4) Leadership has a positive and significant influence on job satisfaction; 5) Organizational Commitment has a positive and significant influence on Job Satisfaction; 6) Leadership has an indirect influence on Organizational citizenship behavior through Job Satisfaction; 7) Organizational Commitment has an indirect influence on Organizational citizenship behavior through Job Satisfaction.